Adult-onset methylenetetrahydrofolate reductase C677T mutation and its repercussion: A case report (Indian Journal of Case Reports, 2024)
Methylenetetrahydrofolate reductase (MTHFR) is an enzyme that converts homocysteine into methionine by catalyzing the conversion of 5,10-methyltetrahydrofolate into 5methyltetrahydrofolate. Deep vein thrombosis, coronary artery disease, peripheral vascular thrombosis, and cerebrovascular thrombosis are attributed to homozygous MTHFR mutations. We describe here a case of a 42-year-old male, who presented to us with subdural hemorrhage following systemic thrombolysis for pulmonary embolism. He was found to have hyperhomocysteinemia as a result of homozygous MTHFR C677T mutation. He underwent left fronto-temporo-parietal decompressive craniectomy and hematoma evacuation with the placement of a free bone flap in the right anterior abdominal wall and placement of an IVC filter to prevent recurrent venous thromboembolism. He was started on Vitamin B12, pyridoxine, and folic acid supplementation and was discharged in a stable condition with a plan for cranioplasty at a later date.